Impact assessment of large-scale penetration of permanent magnet synchronous generators on power quality - Ntsadu, Ntlahla (Department of Electrical Engineering, 2018)
Wind power generation has gained a large share in the renewable energy market over the past few years. This study investigates the impact of large scale penetration of permanent magnet synchronous generator (PMSG) based wind turbines on power quality of the grid. PMSGs are attractive due to the absence of a gearbox in the drive-train, which results in lower maintenance costs and higher reliability. Moreover, the advancements in power electronics have facilitated PMSGs to generate optimal power at varying wind speed conditions. This is achieved through the use of maximum power point tracking algorithms. The drawbacks of PMSG-based wind energy systems are that they inject harmonics into the network and cause flicker as well as other power quality issues. Despite these disadvantages, the grid code requires that PMSGs stay connected to the grid even under grid disturbances. This is because the reactive power control capability of PMSG-based wind energy systems can actually assist with voltage support. It will be shown in this study that disconnecting large scale PMSGs based wind turbines during grid disturbances has a detrimental effect on transient stability of the grid. This study will show that PMSG-based wind energy systems improve transient stability and assist in voltage support through reactive power control. Moreover, the impacts of large scale PMSG based wind turbines on power quality of the grid can be reduced by various means, which are also addressed in the study.